Analisis produktivitas unit usaha pada industri kecil pandai besi di Desa Koto Padang Kecamatan Tanah Kampung Kota Sungai Penuh - Elsya Ramadhani; Purwaka Hari Prihanto; Hardiani Hardiani (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2020)
This study aims to analyze the productivity of business units and to analyze the effect of business capital, working capital, and labor on the productivity of business units in small blacksmith industries in Koto Padang Village, Tanah Kampung Subdistrict, Sungai Penuh City. This research is quantitative research and the type of data used in this study is primary data in the form of cross-section data on productivity levels, business capital variables, working capital, and labor. The sample in this study amounted to 43 respondents with the instruments used in the form of questionnaires and interviews. The data obtained were processed using SPSS20 with multiple linear regression analysis methods. The results of the study with a significant level of 10%, the business capital variable obtained a significant level of 0.060 with a significant value less than 0.1, meaning that business capital affects productivity. The working capital variable obtained a significant level of 0.037 with a significant value less than 0.1, meaning that working capital affects productivity. And the labor variable obtained a significant level of 0.288 with a significant value greater than 0.1, which means that the number of workers does not affect productivity. Keywords: Productivity, Business capital, Working capital, Labor.